Qualitative performance and economic analysis of low cost solar fish driers in Sub-Saharan Africa - Mustapha, Moshood Keke; Salako, Abdulbashir Femi; Ademola, Sunmola Kayode; Adefila, Ifeoluwa Abimbola (Journal of Fisheries, 2014)
Qualitative performance and economic analysis of five low cost solar driers were evaluated at the Zoology and Physics Laboratories of the University of Ilorin, Ilorin, Nigeria. The solar driers were constructed from mosquito net, plastic, aluminum and glass with black stone inserted in it. The driers were found to be better than the other driers because they are cheap, reliable, safe to use, easy to repair, well insulated, and cost effective. The solar driers are compact, efficient with drying of fish with lowest moisture content achieved within a few days and the dried products of good quality, with long shelf life, highly acceptable to consumers. The driers save man-hour, money, use renewable energy, with no operational or maintenance costs. The driers have a long life span, with net income to fisher folks very high and the payback time for the driers very low. The adoption of the driers will contribute to the economy of rural populace in the developing countries where there is no electricity and the challenges of deforestation are becoming prominent. The improved low cost solar driers will ensure food safety and security and assist in combating climate change resulting from burning of wood and fossil fuel.